Fast and Slow Inhibition in the Visual Thalamus Is Influenced by Allocating GABAA Receptors with Different γ Subunits - Ye, Zhiwen; Yu, Xiao; Houston, Catriona M.; Aboukhalil, Zahra; Franks, Nicholas P.; Wisden, William; Brickley, Stephen G. (Frontiers in Cellular Neuroscience, 2017)
Cell-type specific differences in the kinetics of inhibitory postsynaptic conductance changes (IPSCs) are believed to impact upon network dynamics throughout the brain. Much attention has focused on how GABAA receptor (GABAAR) alpha and beta subunit diversity will influence IPSC kinetics, but less is known about the influence of the gamma subunit. We have examined whether GABAAR gamma subunit heterogeneity influences IPSC properties in the thalamus. The gamma2 subunit gene was deleted from GABAARs selectively in the dorsal lateral geniculate nucleus (dLGN). The removal of the gamma2 subunit from the dLGN reduced the overall sIPSC frequency across all relay cells and produced an absence of IPSCs in a subset of relay neurons. The remaining slower IPSCs were both insensitive to diazepam and zinc indicating the absence of the gamma2 subunit. Because these slower IPSCs were potentiated by DMCM, we propose these IPSCs involve gamma1 subunit-containing GABAAR activation. Therefore, subunit heterogeneity appears to influence the kinetics of GABAAR-mediated synaptic transmission in the visual thalamus in a cell-selective manner. We suggest that activation of gamma1 subunit-containing GABAARs give rise to slower IPSCs in general, while faster IPSCs tend to be mediated by gamma2 subunit-containing GABAARs.